Pathology and biology of radiation-induced cardiac disease - Tapio, Soile (Journal of radiation research, 2016)
Heart disease is the leading global cause of death. The risk for this disease is significantly increased in populations exposed to ionizing radiation, but the mechanisms are not fully elucidated yet. This review aims to gather and discuss the latest data about pathological and biological consequences in the radiation-exposed heart in a comprehensive manner. A better understanding of the molecular and cellular mechanisms underlying radiation-induced damage in heart tissue and cardiac vasculature will provide novel targets for therapeutic interventions. These may be valuable for individuals clinically or occupationally exposed to varying doses of ionizing radiation.